Visualization of Spirochetes by Labeling Membrane Proteins With Fluorescent Biarsenical Dyes - Hillman, Chadwick; Stewart, Philip E.; Strnad, Martin; Stone, Hunter; Starr, Tregei; Carmody, Aaron; Evans, Tyler J.; Carracoi, Valentina; Wachter, Jenny; Rosa, Patricia A. (Frontiers in Cellular and Infection Microbiology, 2019)
Numerous methods exist for fluorescently labeling proteins either as direct fusion proteins (GFP, RFP, YFP, etc. - attached to the protein of interest) or utilizing accessory proteins to produce fluorescence (SNAP-tag, CLIP-tag), but the significant increase in size that these accompanying proteins add may hinder or impede proper protein folding, cellular localization, or oligomerization. Fluorescently labeling proteins with biarsenical dyes, like FlAsH, circumvents this issue by using a short 6-amino acid tetracysteine motif that binds the membrane-permeable dye and allows visualization of living cells. Here, we report the successful adaptation of FlAsH dye for live-cell imaging of two genera of spirochetes, Leptospira and Borrelia, by labeling inner or outer membrane proteins tagged with tetracysteine motifs. Visualization of labeled spirochetes was possible by fluorescence microscopy and flow cytometry. A subsequent increase in fluorescent signal intensity, including prolonged detection, was achieved by concatenating two copies of the 6-amino acid motif. Overall, we demonstrate several positive attributes of the biarsenical dye system in that the technique is broadly applicable across spirochete genera, the tetracysteine motif is stably retained and does not interfere with protein function throughout the B. burgdorferi infectious cycle, and the membrane-permeable nature of the dyes permits fluorescent detection of proteins in different cellular locations without the need for fixation or permeabilization. Using this method, new avenues of investigation into spirochete morphology and motility, previously inaccessible with large fluorescent proteins, can now be explored.